PENGARUH FASILITAS BELAJAR DI RUMAH , MINAT BELAJAR DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR KOMPUTER AKUNTANSI - Risda Zulfia; Efrizal Syofyan (Program Magister Pendidikan Ekonomi (S2), 2015)
The purpose of this research is recognizing the effects of learning facility at home, the willing ness and motivation of learning to the learning output of accountancy computer on the eleventh students of SMK in Agam regency directly even indirectly.The population of this research is all economic students in amounts of 228 students. The sample of this research is 70 students. The method of sampling was done by using proportionated random sampling. The data collection was done by filling in questionaire. The data analysis used “Parth Analysis”. The data processing was done by using spss.17.0 version.The resolt of this research that there was significant effects, among (1) learning facility at home to learning motivation,(2) learning facility at home to learning out put,(3) The willing ness of learning to learning out put,(4) The learning motivation to learning out put,(5) In general the amount of effect was known 48,53 % directly or indirectly mean while 41,47 % of the total was influenced by other factors which was not done on this research. Key words: Learning Out Put , Learning Motivation , Willingness of Learning and Learning Facility at Home.